Pemasaran Digital Siswa SMKN 1 Sumbawa Berbasis Instagram dan Facebook - Nuryani, Hanifa Sri; Nuryadi, Halid; Muhammad Rizqi, Reza (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
aligning student competencies with the accelerating global digital economic transformation. At State Vocational High School (SMKN) 1 Sumbawa Besar, specifically within the Online Business and Marketing (BDP) program, a significant discrepancy exists between students' extensive social media engagement and their deficient literacy in utilizing these platforms for productive, commercial purposes. Most students perceive digital platforms exclusively as entertainment and passive interaction tools. This article examines the implementation and outcomes of a community service program designed to restructure paradigms and enhance technical digital marketing competencies through Instagram and Facebook platforms. Grounded in promotional mix and integrated marketing communication theories, the approach positions social media as a strategic instrument for creating value propositions and building measurable customer engagement. The Participatory Action Research (PAR) framework encompassed three phases: situational analysis through observation, intensive workshops incorporating hands-on training in Instagram visual content management and Facebook Ads, and comprehensive evaluation. The program engaged 60 students from grades X and XI. Quantitative evaluation through pre-test and post-test instruments revealed significant success in knowledge transfer and skill acquisition. The mean cognitive and technical comprehension score increased by 27.2 points, from 55.4 to 82.6 upon completion. Furthermore, the initiative successfully transformed students' psychological orientation from passive consumers to strategic content producers capable of designing and evaluating data-driven digital advertising campaigns. The integration of practical digital marketing training proved effective in equipping vocational students with industry-relevant 21st-century competencies. Findings underscore the imperative for educational stakeholders to formally integrate advanced digital marketing modules and advertising budget allocations into the regular curriculum and Teaching Factory (TEFA) units, thereby ensuring sustainable digital entrepreneurship competencies for advancing future micro-business ecosystems.